2005
DOI: 10.1143/jjap.44.539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultraviolet Light Irradiation on Structure and Electrochemical Properties of Iron Surface

Abstract: The effect of ultraviolet light (UV) irradiation (254 nm, 0.8 mW/cm2) on air-formed oxide films and passivated films on iron was investigated by electrochemical methods and scanning tunneling microscopy (STM), in particular with respect to surface micro/nanostructures and the surface protective property. An as-deposited film appeared uniformly flat after UV irradiation for 2–4 h, which is associated with a decrease in current density. UV irradiation for 1–4 h assisted N-dodecylhydroxamic acid (DHA) molecules t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, several studies have also shown that the higher anodic potential can result in the increase of the roughness and the formation of micropores on the surface of Ti and its alloy [12,13]. As is known to all, a material with a flat and dense surface may have a better corrosion resistance [14]. Sivaet al [15] studied the effect of surface roughness of industrial pure titanium on corrosion resistance, and electrochemical tests revealed the lower the surface roughness of industrial pure titanium, the better its corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have also shown that the higher anodic potential can result in the increase of the roughness and the formation of micropores on the surface of Ti and its alloy [12,13]. As is known to all, a material with a flat and dense surface may have a better corrosion resistance [14]. Sivaet al [15] studied the effect of surface roughness of industrial pure titanium on corrosion resistance, and electrochemical tests revealed the lower the surface roughness of industrial pure titanium, the better its corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…6 the good STM images were easier to be observed after UV-irradiation for 2 h, compared with just anodization at 1500 mV, and the terrace wider than 6 nm was observed. It had been reported that step-terrace structures were easily generated on the electrochemically passivated surfaces, and UV-irradiation normally produced electron-hole pairs, which electrolyze water on the passive film and generate oxygen [5]. And it is also reported that UV-irradiation can also remove electrons from oxygen in oxide passive films and separate an oxide passive film into metal and oxygen, and the excessively long or strong UV-irradiation under dry condition may break down oxide molecules instead of water molecules to a rough oxide surface in nanoscale[6].…”
Section: Effect Of Uv-irradiation On Microstructures Of Anodized Tita...mentioning
confidence: 99%
“…There are many studies focusing on the structure changes of metal oxide film induced by UV-light [24,31]. The effect of VUV (UV in vacuum conditions) pretreatment on the crystallization of anatase in sol-gel-derived TiO 2 precursor films was reported by Nakajima et al [32], and it was found that VUV irradiation changed the film structure and the degree of the microstructure evolution depends on the intensity and duration of the VUV irradiation [32].…”
Section: E Microstructure Of the Native Ti Oxides Surfacementioning
confidence: 99%